KOMPARASI GAYA KEPEMIMPINAN NABI MUSA DAN FIR’AUN DALAM PENDIDIKAN KARAKTER - Doni Wahidul Akbar; Fitri Liza (STIT AL-AMIN KREO TANGERANG, 2023)
Leadership style is a characteristic of a leader who sits on his throne. Every leader will have a different leadership style. This research will try to analyze the leadership styles of prophets Moses and Pharaoh contained in the Old Testament Bible, the Qur'an, and ancient manuscripts. It is very interesting to combine the leadership styles of prophets Moses and Pharaoh which are full of complexity and then applied in character education. It aims to provide new nuance for educators to implement leadership styles in character education. a qualitative method with a descriptive analysis approach used in this research and collaborating comparative method to get a comparison of leadership styles that should be used as a basis and which should not be used as a basis for an educator. Prophet Moses and Pharaoh can be likened to positive and negative things. How not, if you hear the name Pharaoh it will lead to a negative paradigm. However, there are several leadership styles of Pharaoh that can be imitated. 13 leadership styles can be practiced in character education and there are 6 leadership styles that should not be exemplified for students. The results of this study can make the motivation of educators in improving their leadership style in teaching